Dolutegravir-based antiretroviral therapy-associated hyperglycemia in persons living with human immunodeficiency virus in Niger: a multicentric cross-sectional study - Yacouba, Abdourahamane; Sidibe, Ramatou; Dalla, Aboubacar-Sidick Chegou Sonouchi; Issa, Ali Inoussa; Saley, Sahada Moussa; Tapha, Ounoussa; Bassirou, Abdou Natali; Doutchi, Mahamadou; Brah, Souleymane; Abdoul-Wahab, Idrissa Massi; Nouhou, Yacouba; Amidou Ganda, Oumi-Ramatou; et al. (Frontiers in Virology, 2026)
BackgroundGrowing evidence from clinical and experimental research suggests that dolutegravir is associated with hyperglycemia. This study aimed to determine the prevalence of hyperglycemia and its associated factors among persons living with human immunodeficiency virus (PLWH) on dolutegravir-based antiretroviral therapy in Niger.MethodologyThis was a retrospective multicentric cross-sectional study carried out using data from PLWH who had been examined between January 2022 and June 2024. Data were collected from July to September 2024. PLWH aged 18 years or older who had been on dolutegravir-based antiretroviral therapy for more than three months were enrolled in the study. Hyperglycemia was defined as a fasting plasma glucose level ≥7.0 mmol/L. A multivariable logistic regression analysis was conducted in RStudio version 4.4.1 to identify factors associated with hyperglycemia. Variables with a p-value less than 0.05 were considered statistically significant.ResultsA total of 633 records were reviewed during the study period, of which 39.0% (n = 247) had baseline blood glucose levels and were included in this analysis. The mean age of patients was 38.9 ± 11.8 years. More than half of the patients (60.5%; n = 101) had a normal body mass index. The mean duration of the dolutegravir-based regimen was 13.9 ± 7.05 months. The prevalence of hyperglycemia was 36.4% (n = 51). In multivariate analysis, patients with primary (adjusted Odds ratio (aOR): 8.26; 95% CI: 1.47-62.00, p=0.024), secondary (aOR: 6.29; 95%CI: 1.12-48.28; p=0.051), and tertiary (aOR: 9.39; 95%CI: 1.34-89.92; p=0.034) educational levels, patients with a history of personal hypertension (aOR: 4.24; 95% CI: 1.17-17.18; p = 0.033) were significantly associated with hyperglycemia among PLWH on dolutegravir-based ART regimens.ConclusionThe prevalence of hyperglycemia among PLWH on dolutegravir-based antiretroviral therapy regimens was relatively high in Niger. Educated PLWH and hypertension were identified as risk factors for hyperglycemia. Baseline and periodic monitoring of plasma glucose might be required in antiretroviral therapy containing dolutegravir care in Niger.